Manajemen Pengadaan Peralatan Multimedia Audio Visual di SMA Negeri 3 Solok - Rahma Fitri Wahyuni; Jasrial Jasrial; Nelfia Adi; Enceria Damanik (CV. ITTC INDONESIA, 2026)
This study is motivated by the efforts of SMA Negeri 3 Solok in procuring audio-visual multimedia equipment. The purpose of this research is to describe the management process of audio-visual multimedia equipment procurement at SMA Negeri 3 Solok, which includes planning, organizing, implementation, and supporting factors. This study used a qualitative approach with a descriptive method. Data were collected through in-depth interviews, observation, and documentation study. Data validity was examined using source, technique, and time triangulation. Data analysis included data reduction, data presentation, and conclusion drawing. The results of the study show that: (1) The planning of audio visual multimedia equipment procurement was carried out through needs identification and internal deliberation; (2) Organizing was implemented through competency based task distribution without forming a formal bureaucratic structure; (3) The procurement implementation was conducted through a grant funding mechanism with stages of proposal submission, communication, and physical verification upon goods receipt; (4) The main supporting factors were leadership commitment, human resource competence, and the availability of grant funds.